2019
DOI: 10.15835/nbha47411755
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Effects on Hyssop (Hyssopus officinalis L.) Morphology and Cd Uptake in Relation to Substrate Acidity/Alkalinity

Abstract: Hyssop (Hyssopus officinalis), is a herb with a wide range of use in food preparation and herbal medicine. It is a perennial shrub through which pollutants such as Cd may enter the human food chain Therefore, the aim of this research was to examine the extent to which Cd added to the growth substrate is accumulated by hyssop plants and whether Cd affects the plant’s morphology. Hyssop plants were grown in pots containing a uniform mixture of either moderately acidic or slightly alkaline substrate consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Note: see Figure 1 In both experimental periods shoot, root and total Cd uptake by valerian plants increased with increasing Cd application (Figures 3,4,5,6). These results are in accordance with those reported by Akoumianaki-Ioannidou et al (2019) for hyssop. Moustakas et al (2001) and Akoumianakis et al (2008) reported that Cd application increased Cd concentrations in the leaves of lettuce, radish and cucumber, and in endive and rocket, respectively.…”
Section: St Experimental Periodsupporting
confidence: 94%
See 2 more Smart Citations
“…Note: see Figure 1 In both experimental periods shoot, root and total Cd uptake by valerian plants increased with increasing Cd application (Figures 3,4,5,6). These results are in accordance with those reported by Akoumianaki-Ioannidou et al (2019) for hyssop. Moustakas et al (2001) and Akoumianakis et al (2008) reported that Cd application increased Cd concentrations in the leaves of lettuce, radish and cucumber, and in endive and rocket, respectively.…”
Section: St Experimental Periodsupporting
confidence: 94%
“…In addition, no growth inhibition was detected even though considerable Cd concentrations were found within the plants. Overall, therefore, valerian can be considered a Cd accumulating plant, like hyssop, rocket, endive, lettuce, spinach, turnip grass, celery and cabbage (Bingham et al, 1983;Davis 1984;Akoumianakis et al, 2008;Akoumianaki-Ioannidou et al, 2019). The amount of Cd extractable by DTPA-TEA in the moderately acidic substrate ranged from 0.1 to 0.7 mg kg -1 and from 0.3 to 0.9 mg kg -1 for the 1 st and 2 nd experimental period, respectively (Table 1).…”
Section: St Experimental Periodmentioning
confidence: 99%
See 1 more Smart Citation